WILLINGNESS TO PAY LAHAN PEMAKAMAN UMUM KOTA BANDA ACEH DAN SEKITARNYA - Satriawan, Agung Dwi (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2016)
This study is aimed at analyzing the factors that influence willingness to pay public cemetery in Banda Aceh and surrounding area. This study is conducted in Banda Aceh and surrounding area with housing complex as the samples.Â  Ordinary Least Square (OLS) is employed to find the significant influence between price, income, and distance and willingness to pay. The finding of this study revealed that the three variables are theoretically and statistically significant. Variable price has negative coefficient while income and distance has positive coefficient. From the findings of this study it is suggested to the authority to pay more attention in providing public cemetery which is part of green open space. It is also suggested to further researcher to add other variables that may significantly influence willingness to pay public cemetery.Key words: Willingness to Pay, Public Cemetery, Price, Income, distnce